The heterogeneous effects of China's accession to the world trade organization - Benjamin Jung (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2020)
China's accession to the World Trade Organization (WTO) in 2001 was a massive boostfor the multilateral trading system. We present descriptive evidence on the trade effects of China's WTO accession. Moreover, we combine the most recent approaches from the gravity literature of international trade to provide a causal analysis of the effects of China's WTO accession on bilateral trade with other WTO members. We find that the trade effectis positive on average. Moreover, we document substantial heterogeneity in the trade effects across China's trading partners. These findings seem to be consistent with China's position in global value chains.
urn:nbn:de:bsz:100-opus-18126
Keywords: F13; F14; 330; GATT/WTO; China; international trade; structual gravity